2016
DOI: 10.1159/000450836
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Neutrophil to Lymphocyte Ratio as a Predictor of Intervention in Acute Diverticulitis

Abstract: Background: Neutrophil to lymphocyte ratio (NLR) is a novel biomarker that has been recently studied in diverticulitis. The primary aim of this study was to assess the accuracy of NLR in predicting which patients had complicated diverticulitis and which patients required a radiological or surgical intervention. The accuracy of NLR was compared to C-reactive protein (CRP), white blood cell (WBC) count, neutrophil count and white cell to lymphocyte ratio (WLR). Methods: Details of all patients admitted with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
4
21
1
Order By: Relevance
“…Perhaps the differences between the results are related to the higher intervention rates in that study (20.8%) compared to ours (7.5%). 15 It should be noted that we decided to choose a novel cutoff for NLR and PLR instead of using previous studies' cutoffs due to the large cohort and the possibility to establish new cutoff values that may be more significant than cutoff values used for small cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the differences between the results are related to the higher intervention rates in that study (20.8%) compared to ours (7.5%). 15 It should be noted that we decided to choose a novel cutoff for NLR and PLR instead of using previous studies' cutoffs due to the large cohort and the possibility to establish new cutoff values that may be more significant than cutoff values used for small cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the possible recognition of clinical or biochemical parameters that could be used to identify patients who progress from uncomplicated to complicated AD and to monitor the potential development of complications requiring immediate surgical intervention are matters of debate. Procalcitonin 113 and neutrophil count and white cell to lymphocyte ratio 114 have been proposed as accurate markers to differentiate complicated from uncomplicated diverticulitis, and higher levels of calprotectin, an inflammatory colonic mucosal marker, tend to be associated with more severe AD 25 . Clinical predictors of early recurrences up to 6 months after a first episode of AD appear to be high C-reactive protein (CRP) levels 115 , the presence of systemic inflammatory response syndrome, high pain score, and regular steroid or immunomodulator use 116 .…”
Section: Acute Diverticulitis Managementmentioning
confidence: 99%
“…In this study, the predictive power of the DNI with regards to the need for emergent surgical intervention in patients with acute diverticulitis was significantly higher than that of serum CRP levels, and WBC and neutrophil counts, which are commonly used markers for predicting inflammation and infection in the ED. The diagnostic power of the DNI in predicting the need for emergent surgical intervention in patients with acute diverticulitis was also significantly higher than that of the NLR, which was recently reported as being useful for predicting of surgical intervention in acute diverticulitis [ 13 ]. Even though CT-based imaging severity criteria, including the Hinchey classification and its successive modifications, have been shown to assist in the prediction of the clinical course of diverticulitis [ 23 , 25 , 26 ], the predictive value of the combination of initial DNI and CT was significantly higher than its of only CT and the predictive value of combination of initial DNI and CT was most powerful diagnostic modality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study evaluated the role of the NLR in the setting of acute diverticulitis. They concluded that the NLR was more accurate than CRP levels, and WBC and neutrophil counts in predicting the need for a surgical intervention, which indicates complicated diverticulitis [ 13 ]. The principle of the NLR is that neutrophil levels elevate as part of the inflammatory cascade, whereas lymphocytes are decreased during sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation